774 Prognostication of Civilian Gunshot Wounds to the Head: Internal Validation of the Baylor Score. (April 2023) - Gopakumar, Sricharan; Anand, Adrish; McDonald, Malcolm F.; Cruz-Navarro, Jovany; Karas, Patrick J.; Gopinath, Shankar Prakash
Abstract : INTRODUCTION: Early prognostication of patients with gunshot wounds to the head (GSWH) can identify patients who may benefit from aggressive management. The Baylor score uses patient age, pupil reactivity, Glasgow Coma Scale, and bullet trajectory at initial presentation to predict mortality and functional status at six months and performed well when recently assessed at a separate level 1 trauma center demonstrating external validation of the score. METHODS: Retrospective chart review of patients with GSWH treated at an academic level 1 trauma center between 2008 and 2022 was performed with Baylor score calculated for each patient. Accuracy of the Baylor score in predicting mortality and good functional outcome (Glasgow Outcome Scale score of 4 or 5) was assessed using receiver operating characteristic (ROC) curves and area under the curve (AUC) as measures of performance. RESULTS: A total of 405 patients with GSWH were identified over the 14-year study period (mean age 31.5 years, 88.9% male, 19.5% white). 225 (55.6%) patients died, while 145 (35.8%) had favorable functional outcomes. Mortality rates ranged from 8% for Baylor score 0 to 97% for Baylor score 5, and good functional outcomes ranged from 15% for Baylor score 3 to 87% for Baylor score 0. Baylor score demonstrated good accuracy in prognosticating both mortality (AUC = 0.85) and good functional outcome (AUC = 0.90), though scores 0-2 underestimated favorable outcomes and scores 3-5 underestimated mortality. CONCLUSIONS: The Baylor score is a valuable tool for prognosticating GSWH survival and functional outcome and may aid in guiding treatment and family-centered discussions regarding patient prognosis earlier in the hospital course.